2021
DOI: 10.1136/bjsports-2021-104203
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the risk of SARS-CoV-2 infection, severe COVID-19 illness and COVID-19 related mortality in South Korea: a nationwide cohort study

Abstract: PurposeTo determine the potential associations between physical activity and risk of SARS-CoV-2 infection, severe illness from COVID-19 and COVID-19 related death using a nationwide cohort from South Korea.MethodsData regarding 212 768 Korean adults (age ≥20 years), who tested for SARS-CoV-2, from 1 January 2020 to 30 May 2020, were obtained from the National Health Insurance Service of South Korea and further linked with the national general health examination from 1 January 2018 to 31 December 2019 to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(226 citation statements)
references
References 41 publications
8
179
1
4
Order By: Relevance
“…In a sample of 48,440 patients in the US, PA in compliance with current recommendations was associated with a reduced risk of hospitalization, intensive care unit admission and mortality [7]. Similar results were reported in a nationwide study in South-Korea [8]. Brawner and colleagues found that cardiorespiratory fitness was independently and inversely associated with the risk of COVID-19-related hospitalization [9].…”
Section: Introductionsupporting
confidence: 59%
“…In a sample of 48,440 patients in the US, PA in compliance with current recommendations was associated with a reduced risk of hospitalization, intensive care unit admission and mortality [7]. Similar results were reported in a nationwide study in South-Korea [8]. Brawner and colleagues found that cardiorespiratory fitness was independently and inversely associated with the risk of COVID-19-related hospitalization [9].…”
Section: Introductionsupporting
confidence: 59%
“…Hospitalization criteria should be similar across Air Force military treatment facilities, and potential heterogeneity was accounted for by geographical matching of cases and controls. Furthermore, the use of hospitalization as an indicator of COVID-19 severity is widespread in studies of civilian populations ( 1 , 2 , 6 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are causally or noncausally related to various health-related behaviors, some of which are independently associated with COVID-19 severity. For example, current and former smoking status is associated with disease progression ( 6 ), and physical inactivity increases risk of hospitalization, intensive care unit admission, and mortality ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study in hospitalized patients with COVID-19 that assessed muscle strength on admission observed that the length of hospital stay was significantly shorter among patients in the highest tertile of strength [82]. Recently, a study investigating a cohort of 76,395 South Korean adults found that adults engaging in the recommended levels of PA had a decreased likelihood of SARS-CoV-2 infection, severe COVID-19 illness and COVID-19 related death [83]. In the aforementioned study, the authors argue that enhanced immunosurveillance, delayed onset of immunosenescence and reduced systemic inflammation, all to be discussed here, as possible explanations as immunological effects decreasing the risk of infection and severity due to COVID-19.…”
Section: Effects Of Physical Activity and Exercise On Human Biology In View Of Covid-19mentioning
confidence: 99%